The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14687/jhs.v16i1.5512
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mindfulness-based programs on coping with test anxiety: A systematic review <p>Sınav kaygısıyla başa çıkmada bilinçli farkındalık temelli programların etkiliği: Sistematik bir derleme

Abstract: The research is a systematic review and the purpose of the research is; is the evaluation of experimental and mixed studies designed to examine the effectiveness of mindfulness-based programs applied to coping with test anxiety. In this context, English and Turkish articles and theses published in YOK TEZ, ULAKBIM, Google Academic and EBSCOhost databases between 2000 (January) and 2018 (April) have been systematically screened. In the study, mindfulness based interventions for test anxiety, mindfulness based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Due to its nature which stems from the meditation studies in Eastern culture, mindfulness is that the individual connects with the experienced moment by directing his/her attention and conscious in a deep, acquiescent and non-judgmental way towards the experiences lived in the moment which can be understood completely solely by experiencing it (Brown & Ryan, 2003;Chambers et al, 2009;İkiz & Uygur, 2019;Kabat-Zinn, 2003) so that, mindfulness can be conceptualized as a characterization as well (Garland, 2013). Several studies carried out with children and adolescents reveal that the correlation between mindfulness and wellbeing as well as life satisfaction is high (Brown, West, Loverich, & Biegel, 2011;İkiz & Uygur, 2019) and that the correlation between mindfulness and psychological problems such as depressive emotional state, anger and addiction is low (Black, Sussman, Johnson & Milam, 2012;Brown et al, 2011;Calvete, Sampedro, & Orue, 2014). Also, it is reported that mindfulness in adolescents is negatively correlated on a high level with individual's having problem in controlling their behavior (Güldal, 2019).…”
Section: Importance Of Needs and Mindfulness On Social Media Use In A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its nature which stems from the meditation studies in Eastern culture, mindfulness is that the individual connects with the experienced moment by directing his/her attention and conscious in a deep, acquiescent and non-judgmental way towards the experiences lived in the moment which can be understood completely solely by experiencing it (Brown & Ryan, 2003;Chambers et al, 2009;İkiz & Uygur, 2019;Kabat-Zinn, 2003) so that, mindfulness can be conceptualized as a characterization as well (Garland, 2013). Several studies carried out with children and adolescents reveal that the correlation between mindfulness and wellbeing as well as life satisfaction is high (Brown, West, Loverich, & Biegel, 2011;İkiz & Uygur, 2019) and that the correlation between mindfulness and psychological problems such as depressive emotional state, anger and addiction is low (Black, Sussman, Johnson & Milam, 2012;Brown et al, 2011;Calvete, Sampedro, & Orue, 2014). Also, it is reported that mindfulness in adolescents is negatively correlated on a high level with individual's having problem in controlling their behavior (Güldal, 2019).…”
Section: Importance Of Needs and Mindfulness On Social Media Use In A...mentioning
confidence: 99%
“…well-being and life satisfaction (Brown, West, Loverich, & Biegel, 2011;İkiz & Uygur, 2019) and a low correlation with psychological problems such as depressive mood, anger and addiction (Black, Sussman, Johnson, & Milam, 2012;Brown et al, 2011;Calvete, Sampedro, & Orue, 2014). Through social media adolescents engage in a variety of social activities, such as self-disclosure and interaction with others.…”
mentioning
confidence: 99%
“…In addition, in an ACT intervention study on math anxiety, participant’s anxiety about math lesson significantly decreased (Zettle, 2003). In addition, a mindfulness-based intervention program, which is one of the ACT techniques, was reported to have reduced test anxiety (İkiz & Uygur, 2019). Moreover, in a recent study (using 11 students in each condition) carried out before the pandemic (Yapan et al, 2021), both CBT and ACT interventions were effective at reducing test anxiety in 12 th grade Turkish students compared to a control group, and the therapeutic effects of these interventions were also maintained one and 3 months’ post-intervention.…”
Section: Introductionmentioning
confidence: 99%